Fixed asset accounting analysis on Pt. Compacto Solusindo Pekanbaru - Antung Pratama (Institute of Accounting Research and Novation (IARN), 2023)
According to PSAK No. 16 of 2009 revised 2007 Article 16 says that fixed assets are tangible assets acquired in the form of ready-to-use or built beforehand, which are used in company operations, are not intended to be sold in the course of the company's normal activities and have a useful life. more than one year. The research was conducted at PT Compacto Solusindo Pekanbaru with the address Jalan Soekarno Hatta No.218 Pekanbaru.The purpose of this study is to find out that the recording of fixed assets by the company is in accordance with the applicable accounting principles, namely PSAK No. 16 of 2009 concerning Fixed Assets. according to the rules stated in PSAK No.16 the value of the building cannot be combined with the value of the land, because the land is not depreciated while the building experiences depreciation every year. residual value of the item.The author suggests that in compiling reports on depreciation of company assets, it should be guided by the applicable provisions, namely PSAK No. 16 concerning fixed assets so that there are no errors in calculating the actual value of fixed assets.